Agglomeration and Growth: Evidence from the Regions of Central and Eastern Europe - Johanna Vogel (European Regional Science Association (ERSA), 2012)
This paper examines the empirical relationship between agglomeration and economic growth for a panel of 48 Central and Eastern European regions from 1995 to 2006. By agglomeration, we mean the within-regional concentration of aggregate economic activity, which we measure using the 'topographic' Theil index developed by Bruelhart and Traeger (2005). A transitional growth specification à la Mankiw, Romer and Weil (1992) is augmented with this index and estimated using panel data methods that account for endogeneity and spatial dependence. Our empirical analysis provides evidence of a positive effect of agglomeration as measured by the topographic Theil index on long-run income levels. A one standard-deviation increase in agglomeration is estimated to raise steady-state income per capita by 15%. While this effect is sizeable, it may also imply a trade-off between regional development and within-regional equality for Central and Eastern Europe.
Keywords: R11; R12; C23; O52; 330; Agglomeration; regional growth; Central and Eastern Europe; spatial econometrics; panel data econometrics